2021
DOI: 10.7759/cureus.18158
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Weight Self-Stigma and Quality of Life Among Youth in the Jazan Region, Saudi Arabia

Abstract: Background: Studies on the role of weight self-stigma on the quality of life of young adults are limited. Therefore, the present study aimed to examine the relationship between different forms of weight selfstigma (self-devaluation and fear of enacted stigma) and the quality of life among Saudi youth in the Jazan region.Methods: A cross-sectional study was performed using a sample of 399 participants who were invited through social media platforms. We used Arabic, validated versions of the weight self-stigma q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The factorial structure is identical to that of the original English WSSQ, indicating that it is useful in cross-cultural research [26]. The selfdevaluation section of the WSSQ had an internal consistency of .840, while the fear of enacted stigma had revealed .876 [27]. Thereupon, the Arabic WSSQ appears to be a valid tool for assessing weight-related self-stigma among people who speak Arabic.…”
Section: Weight Stigmatization Assessment (Wssq)mentioning
confidence: 94%
“…The factorial structure is identical to that of the original English WSSQ, indicating that it is useful in cross-cultural research [26]. The selfdevaluation section of the WSSQ had an internal consistency of .840, while the fear of enacted stigma had revealed .876 [27]. Thereupon, the Arabic WSSQ appears to be a valid tool for assessing weight-related self-stigma among people who speak Arabic.…”
Section: Weight Stigmatization Assessment (Wssq)mentioning
confidence: 94%
“…The questionnaire was developed and validated as described later, guided by the Obese Stereotypes and Causes of Obesity Scale 14 and the Anti-fat Attitudes Test (AFAT). 15 The tool consisted of three sections. The first section included nine questions about sociodemographic characteristics: gender, age, nationality, level of education, marital status, monthly income, workplace, height (m), and body weight (kg).…”
Section: Methodsmentioning
confidence: 99%
“…13 .Another study including 1,459 participants found that obese people in Saudi Arabia face stigmatisation that is manifested in different forms, including primarily negative behaviours (25.6%), bad comments (25.4%), and physical barriers (25.2%). 14 Interestingly, Khodari, et al 15 recently explored weight selfstigma in Jazan (in the Southern Region of Saudi Arabia) and demonstrated that it was positively associated with BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Asian countries has highlighted the association between weight stigma, abnormal eating attitudes and behaviors, and mental health outcomes. In Saudi Arabia, a robust significant correlation was observed between weigh self-stigma scores on measures of depression, anxiety, and stress scale scores among youths [ 8 ].…”
Section: Introductionmentioning
confidence: 99%